Does aid for education educate children? Evidence from panel data - Axel Dreher; Peter Nunnenkamp; Rainer Thiele (ETH Zurich, KOF Swiss Economic Institute, 2006)
This paper empirically analyzes the impact of aid on education for about 100 countries over the period 1970 - 2005. We estimate a system of equations to test whether and to what extent the impact of sector-specific aid on educational attainment depends on (i) the extent to which aid adds to overall educational expenditure of the recipient government, (ii) the strength of the link between government expenditure and education, (iii) the quality of institutions in the recipient country, and (iv) whether aid encourages institutional reforms. According to our results, aid significantly increases primary school enrolment. This result is robust to the method of estimation, employing instruments to control for the endogeneity of aid, and the measure of institutional quality employed. The degree of institutional quality, however, has no robust impact on this relationship.
Keywords: 330; Bildungspolitik; Entwicklungshilfe; Wirtschaftspolitische Wirkungsanalyse; Bildungsverhalten; Schätzung; Welt